Trophoblast type-specific expression of senescence markers in the human placenta. (15th September 2019) - Higuchi, Shotaro; Miyamoto, Tsutomu; Kobara, Hisanori; Yamada, Satoshi; Asaka, Ryoichi; Kikuchi, Norihiko; Kashima, Hiroyasu; Ohira, Satoshi; Shiozawa, Tanri
Abstract: Objectives: Cell senescence is irreversible cell cycle arrest. The human placenta is a unique organ that grows and matures during pregnancy until 40 weeks of gestation. However, the role of senescence in placental villi, particularly in the two types of trophoblast, has not yet been elucidated in detail. Therefore, we herein investigated the expression of cell senescence-related markers in trophoblast. Methods: Seventy normal placental tissues were used. The expression of senescence-associated beta-galactosidase (SA-β-gal), cell senescence-related markers (p16, p21, and promyelocytic leukemia; PML), and a growth marker (MCM2) was immunohistochemically examined. The expression of these markers in BeWo cells before and after cell fusion using forskolin was also investigated. Results: The expression of MCM2 is detected in cytotrophoblast (CT). The expression of SA-β-gal in CT is strong in the first and second trimesters, but weaker in the third trimester. Syncytiotrophoblast (ST) are negative in the first and second trimesters, but become positive in the third trimester. The immunohistochemical expression of p16, p21, and PML is stronger in CT than in ST throughout pregnancy. Furthermore, the expression of these markers in ST significantly increases as pregnancy advances. The expression of SA-β-gal, PML, and p21 in BeWo cells is stronger after than before cell fusion. Conclusions: The proliferation and senescence of CT occurred in early to mid-pregnancy in association with syncytial fusion, while senescence was observed in ST in late pregnancy. This coordinated trophoblastic senescence may be essential for maintaining placental function. Highlights: Senescence initially occurs in cytotrophoblast in the first/second trimesters. Cytotrophoblastic senescence is associated with syncytial fusion. Senescence is observed in syncytiotrophoblast in the third trimester. This coordinated senescence may be essential for maintaining placental function.